2000
DOI: 10.1128/jcm.38.4.1651-1655.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing and Exopolysaccharide Biosynthesis of Burkholderia cepacia Isolates from a Portuguese Cystic Fibrosis Center

Abstract: This work describes the first epidemiological survey ofBurkholderia cepacia involved in pulmonary infections among the Portuguese population with cystic fibrosis (CF) who attended the major CF treatment Center in Lisbon at Sta. Maria Hospital from 1995 to the end of 1997. The characterization of the genomic relatedness of the isolates was based on the analysis of their ribopatterns (withEcoRI) followed by construction of a ribotype-based phylogenetic tree. This study was complemented with macrorestriction frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…The growth of the strains was analyzed in rich media (LB without salt) and minimal media (ABC). For the assessment of EPS production, a cotton swab was plunged in a bacterial suspension with an OD 600 0.5 and streaked on modified YEM plates (1% mannitol, 0.06% yeast extract) ( Richau et al, 2000 ). The plates were kept for 72 h at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…The growth of the strains was analyzed in rich media (LB without salt) and minimal media (ABC). For the assessment of EPS production, a cotton swab was plunged in a bacterial suspension with an OD 600 0.5 and streaked on modified YEM plates (1% mannitol, 0.06% yeast extract) ( Richau et al, 2000 ). The plates were kept for 72 h at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…The CF isolate B. cepacia strain IST408, isolated from a Portuguese CF patient with no registered case of cepacia syndrome (Cunha et al ., 2003). IST408 produces high amounts of EPS (Richau et al ., 2000; Cunha et al ., 2004), whereas IST408‐SS1 ( bce F::Tn Mod ‐KmO) and IST408‐SS3 ( bce I::Tn Mod ‐KmO carry disrupted putative polymerase or putative tyrosine autokinase encoding genes respectively, both in the EPS gene cluster bce , resulting in EPS‐negative phenotypes. The B. cenocepacia CF isolate H111 and its isogenic mutant H111‐I, functionally defective in the quorum‐sensing system (Huber et al ., 2001).…”
Section: Methodsmentioning
confidence: 99%
“…For infection, bacterial suspensions in phosphate‐buffered saline (PBS) were prepared. Bacterial colonies on Pseudomonas Isolation Agar (PIA, Difco, Hamburg, Germany) were inoculated in 10 ml of liquid S medium (Richau et al ., 2000), and incubated for 20 h at 37°C with shaking (200 r.p.m.). Then, bacteria were harvested by centrifugation and resuspended in PBS at aconcentration of 1 × 10 3 cfu per 50 μl.…”
Section: Methodsmentioning
confidence: 99%
“…Polysaccharide-conjugated vaccines are already in use, such as the pneumococcal vaccine and conjugated vaccines to prevent meningococcal disease. Bcc are known to produce various extracellular polysaccharides, including cepacian and others [ 28 , 29 , 30 , 31 ]. Several roles related to stress resistance and protection of the pathogen from the immune system have been attributed to cepacian, but no studies on the possible use as a vaccine has been reported so far.…”
Section: Which Is the Best Type Of Vaccine For Bcc?mentioning
confidence: 99%